GREEN MARKETING APPLICATION STRATEGY FOR INCREASING CONSUMER SATISFACTION (CASE STUDY IN FAST FOOD BUSINESS COMPANY GROUP AT MALL KARAWANG) - Retnosary, Rieke (LPPM Universitas Buana Perjuangan Karawang, 2015)
Green marketing is not something new in business. Nowdays, environmental issues become the best opportunity in the marketing strategy. Awearness about environtmental and save the earth become one chance from our responsibility. Environmental damage has become everybody concern, including unit business interst fast food at Karawang Mall. In practice, not all units conducting green issues, but most consumer producst using packaging that can biodegrade in a shoorter time. Research purposes to obtain empirical evidence and find clarity phenomena and conclusions about Green Marketing Strategy For Increasing Customer Satisfaction Case Study In Fast Food Business Company Group At Mall Karawang espacially in environmantally friendly food packaging. This research is expected to contribute to the develpment of economics, especially marketing management. Research conducted on 60 speakers as costumers at fast food group at Mall Karawang using qualitative methods with a naturalistic approach. Data is narrative, descriptive, field notes according to interviews and dokumentation, and make conclusions and recomendations. The results of the analysis of research data, it is concluded as follows : 1. Application of green marketing strategies carried out by business in the Mall Karawang were overlooked by the customers due to perceived lack of information. 2. Customer satisfaction is not obtained from the application of the strategy management of green marketing fast food business group at Mall Karawang but service strategy and menu options. 3. Customers tend to come back even if green marketing strategy is not done because of three basic lean namely; taste, price, and prestige. 4. Factors which become obstacles in the implemantation of green marketing strategy for customers is that customera do not understand the importance of the strategy undertaken by the management to maintain environtmental balance. This is due to a lack of understanding of management information to customers is not done continously/ constantly. The results of this study, given some recommandations to the fast food business group in Mall Karawang. Key words : green marketing, implementation of strategy green marketing, eco-friendly food packaging, customer satisfaction.